Fatigue life analysis of wind turbine gear with oxide inclusion. Issue 3 (8th December 2020) - Liu, Ran; Sun, Dexin; Hou, Junling; Liu, Fengjun; Li, Qun
Abstract: Considering a great deal of wind turbine gear failure cases, it is shown that the oxide inclusion has been one of the main reasons for the failure of the gear shaft under fatigue loading condition. In this paper, the fatigue behaviour of gears involving oxide inclusion under real operating condition is investigated. A three‐dimensional finite element model for helical gear pair applied in the middle stage of wind power increasing gearbox is established, and the fatigue life of nonmetallic inclusion zone of middle gear shaft is predicted using Miner's theory and real load spectrum of wind power growth gearbox. Then, the effects of several factors (such as the size and position of oxide inclusion and residual stress induced by manufacturing) on the fatigue life of gears with inclusion are studied. The results show that both inclusion size and position have great influence on the fatigue life of gears, and the compress residual stress will prolong the fatigue life of gears. Furthermore, the critical safety line and safety region of gears with oxide inclusion have been obtained for three representative inclusion positions. The present work is expected to provide a guidance for the engineering design and life safety evaluation of wind turbine gears.